Electrochemistry of Europium(III) Chloride in 3 LiCl – NaCl, 3 LiCl – 2 KCl, LiCl – RbCl, and 3 LiCl – 2 CsCl Eutectics at Various Temperatures. Issue 8 (1st January 2017) - Schroll, Cynthia A.; Chatterjee, Sayandev; Levitskaia, Tatiana G.; Heineman, William R.; Bryan, Samuel A.
Abstract : Here we report the effect of changing the eutectic melt composition on the electrochemical properties of europium(III) chloride under pyroprocessing conditions. Stoichiometry of electron-transfer, redox potentials and diffusion coefficients were determined using various electrochemical and spectroelectrochemical techniques in four different eutectic mixtures (3 LiCl - NaCl, 3 LiCl - 2 KCl, LiCl - RbCl, and 3 LiCl - 2 CsCl) while varying the temperature of the melt. It was determined that Eu 3+ undergoes a one electron reduction to Eu 2+ in each melt at all temperatures evaluated. Within each of the melts a positive shift in the redox potential as well as an increase in the diffusion coefficient for Eu 3+ was observed as the temperature increased. Also observed was a positive shift in the redox potential and increase in the diffusion coefficient for Eu 3+ as the weighted average of the cationic radii the melt composition decreased.